Brothers in Arms: Role of Mental Health Professionals in COVID19 Health Response - Rana, Mowadat Hussain; Rana, Rusham Zahra (Journal of Pakistan Psychiatric Society, 2020)
Health professionals across the world find themselves engaged in humanity’s war against the COVID19 virus1. As frontline soldiers in this war, the doctors, administrators, paramedics, nurses, janitorial staffand sundry, live in a constant state of danger all the while seeing their patients deteriorate, and even die, in spite of their best efforts. The environmental challenges posed by their protective gears, duty hours, paucity or drying up of resources needed to treat patients, weather conditions, and limited opportunities to rest, compound the situation2. Seeing a health team member fall prey to COVID19, generates grief and sometimes inconsolable bereavement. Staying away from family, friends and significant others for days and weeks at end, and then the dread of passing the infection to them, can generate additional alarm and apprehension. The COVID19 has also given rise to financial stress for the doctors who were supporting their meagre salaries through private practice. The unfounded and uncalled for negative propaganda unleashed by an irresponsible media has added insult to injury. The uncertainty about the length of the COVID19 crisis, the lack of evidence based interventions to guide a doctor to treat his infected patients, lack of guidance to work through emergency scenarios, lack of or complete non-availability of senior team members from the ‘battle front’, have all compounded the challenges faced by the frontline health professionals. The ever-increasing workload, as the infection rates continue to surge, lack of adequate nursing staff, the not so rare occurrence of absenteeism, disillusionment and disgruntled attitude of health team members in the middle of the crisis make the health scene of the war arena dicey, and increasingly dangerous. If left unaddressed, these stressors can seriously undermine the clinical acumen, impede judgment and foresight, and even eclipse the cognitive, psychomotor, and affective faculties of health professionals3.